Effects of Fructus Piperis Longi extract on fibrotic liver of gamma-irradiated rats - El-Kabany Hanan; Mansour Somaya (BMC, 2009)
Abstract Background A major biomarker for liver fibrosis is transglutaminase which catalyzes cross-linking of epsilon-amines and alpha-glutamyl residues among amino acids leading to fibrosis. Fructus Piperis Longi is a common herb used in Chinese medicine. The present study evaluates the role of the ethanol extract of Fructus Piperis Longi in the modulation of liver function in liver fibrosis. Methods Plf extract (50 mg/kg) was force-fed to rats every other day 7 days before administration of thioacetamide and/or gamma irradiation. Thioacetamid 200 mg/kg was intraperitoneally administered to rats twice per week for four weeks. Rats were gamma irradiated (2 Gy/week up to a total dose of 8 Gy). Administration of Plf ext was extended during thioacetamid and/or irradiation treatment. Animals were sacrificed. Biochemical parameters in homogenised liver were tested. Results A significant increase in transglutaminase activity and collagen content was recorded in the liver of thioacetamid-treated and/or irradiated rats. Significant increases in lipid peroxides, lipid hydroperoxides and conjugated dienes associated to significant decreases of reduced glutathione content, superoxide dismutase and catalase activities were also recorded. Administration of Plf ext treatment reduced the severity of liver fibrosis and oxidative damage which was substantiated by amelioration of liver function detected by a decrease in serum aspartate aminotransaminase, alanine aminotransferase, alkaline phosphatase, gamma glutamyltransferase activities and bilirubin (total, direct and indirect) content. Conclusion Treatment of the ethanolic extract of Fructus Piperis Longi ameliorated the increase of the activity of tTG enzyme and enhanced antioxidant activities in fibrotic liver.